DEVELOPMENT OF AN ISLAMIC COUNSELING MODEL USING BIBLIOTHERAPY TECHNIQUES WITH E-BOOKS TO IMPROVE ACADEMIC RESILIENCE - Harahap, Ade Chita Putri; Afri, Lisa Dwi (Program Studi Bimbingan dan Konseling Universitas Tunas Pembangunan Surakarta, 2025)
Academic resilience is one of the key elements of success for mathematics education students in facing academic challenges in higher education. This study aims to develop an Islamic Counseling Model using Bibliotherapy e-books to improve the academic resilience of Mathematics Education students. This research is a Developmental Study with a design according to Borg and Gall, which consists of three stages, namely the preliminary study stage, the model development stage, and the model testing stage. The research was conducted at the State Islamic University of North Sumatra. Data collection was carried out using an academic resilience scale and an expert assessment scale. Data analysis was performed using quantitative descriptive analysis to describe the academic resilience of students in the preliminary study stage, followed by Miles and Huberman's qualitative descriptive analysis to describe the feasibility of the Islamic Counseling Model of Bibliotherapy using e-books, and finally, the U-Mann Whitney test was performed to determine the effectiveness of the model. The results showed that 52% of students' academic resilience in education was in the moderate to low category. The feasibility test of the Islamic Counseling Model using the Bibliotherapy Technique with e-books with several experts showed that it was feasible to use. Based on the U-Mann Whitney test results, a sig. value of 0.000 was obtained, so it was concluded that the Islamic Counseling Model using the Bibliotherapy Technique with e-books was effective in increasing the academic resilience of mathematics education students.